Organomentallics - Elschenbroich, Christoph (Germany : Wiley-VCH, 2006)
THE textbook on organometallic chemistry. Comprehensive and up-to-date, the German original is already a classic, making this third completely revised and updated English edition a must for graduate students and lecturers in chemistry, inorganic chemists, chemists working with/on organometallics, bioinorganic chemists, complex chemists, and libraries. Over one third of the chapters have been expanded to incorporate developments since the previous editions, while the chapter on organometallic catalysis in synthesis and production appears for the first time in this form.
Appendix 7117-760p.; Author Index 761-782p.; Subject Index 783-804p.
Keywords: Alkali metals; Transition-metal-atom; Organometallic compounds